(untitled) (GnosisWisdom, 2024)
In the Peruvian criminal system, the lack of motivation for civil reparation is a common evil in reality, since currently judges become arbitrary products of the discretion they have to set civil reparation, where there is no concern for These justice operators adequately motivate the reparation, where it contributes to the deficiency of the criminal process, due to the level of motivation (insufficient or apparent) of the judicial resolutions by the judges. Within the investigation, it was established to determine whether the lack of motivation for civil compensation affects the principle of proportionality in the criminal system. The descriptive method was used, and the survey technique was applied, whose instrument was the questionnaire. The result shows us a significant direct link between lack of motivation and the inadequate use of the principle of proportionality, suggesting that there is an inconsistent application of these principles in judicial decisions on civil reparation. These findings point to the need to review judicial practices to ensure a more consistent and equitable application of the principle of proportionality, which could substantially improve justice and equity in civil reparations assigned in the context studied.